North America - A Set of Agroclimatic Indicators for Identifying Abiotic Stresses (Base of the analogues tool), Calculated Based on Data from the Coupled Model Intercomparison Project Phase 6 (CMIP6), Specifically the Shared Socioeconomic Pathway SSP2-4.5, for the Period 2021-2040. - Mora Argoti, Brayan Alexander (2025)
The purpose for creating these indicators is to perform a similarity analysis of the climatic conditions (heat, drougth and waterlogging stresses) of a specific location versus the climatic conditions where the accessions of the different crops available in Genesys were collected, within the Analogues tool. The above considers climate change scenarios, thus facilitating the adaptation of crops to future conditions.The purpose for creating these indicators is to perform a similarity analysis of the climatic conditions (heat, drougth and waterlogging stresses) of a specific location versus the climatic conditions where the accessions of the different crops available in Genesys were collected, within the Analogues tool. The above considers climate change scenarios, thus facilitating the adaptation of crops to future conditions.The purpose for creating these indicators is to perform a similarity analysis of the climatic conditions (heat, drougth and waterlogging stresses) of a specific location versus the climatic conditions where the accessions of the different crops available in Genesys were collected, within the Analogues tool. The above considers climate change scenarios, thus facilitating the adaptation of crops to future conditions.The purpose for creating these indicators is to perform a similarity analysis of the climatic conditions (heat, drougth and waterlogging stresses) of a specific location versus the climatic conditions where the accessions of the different crops available in Genesys were collected, within the Analogues tool. The above considers climate change scenarios, thus facilitating the adaptation of crops to future conditions.